Climatic conditions and household food security: Evidence from Tanzania. (October 2022) - Randell, Heather; Gray, Clark; Shayo, Elizabeth H.
Highlights: Research on climatic conditions and household food security is limited. In Tanzania, low rainfall is associated with a higher risk of household food insecurity. Households with fewer working age members are particularly vulnerable. Drought tolerant maize and crop insurance may increase resilience to climate change. Abstract: Food security and adequate nutrition are critical for achieving progress toward sustainable development. Two billion people worldwide experience moderate to severe food insecurity, and rates of hunger have increased over the past several years after declining steadily for decades. The FAO attributes this increase in large part to climate change, though empirical evidence on the relationship between climatic conditions and food security remains limited. We examine this question by linking nationally representative longitudinal data from four rounds of the Tanzania National Panel Survey to high-resolution gridded climate data. We then estimate a set of fixed effects regression models to understand the linkages between recent rainy season precipitation and temperature and two indicators of household food security: Food Consumption Score (FCS) and reduced Coping Strategies Index (rCSI). We find that low rainfall—particularly dry and cool conditions—is negatively associated with food security. Moving from a typical rainfall year to a particularly dry one increases the risk of being food insecure on both measures simultaneously by 13 percentage points. This suggests that a lack of rainfall impedes households' ability to access food, likely through reduced agricultural production and increased food prices, leading to lower dietary diversity and food shortages. Vulnerability is higher among households with fewer working age members, suggesting that households with a greater supply of labor can better withstand droughts. As climate change alters precipitation and temperature patterns over the coming decades, policies to increase resilience will be critical for improving food security, particularly among populations heavily reliant on agriculture.